2012
DOI: 10.1161/circulationaha.111.040311
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Vein Graft Failure and Subsequent Clinical Outcomes After Coronary Artery Bypass Surgery

Abstract: Background Vein graft failure (VGF) is common after coronary artery bypass graft surgery, but its relationship with long-term clinical outcomes is unknown. In this retrospective analysis, we examined the relationship between VGF, assessed by coronary angiography 12 to 18 months after coronary artery bypass graft surgery, and subsequent clinical outcomes. Methods and Results Using the Project of Ex Vivo Vein Graft Engineering via Transfection IV (PREVENT IV) trial database, we studied data from 1829 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 28 publications
2
85
0
1
Order By: Relevance
“…1 Although CABG improves survival and symptoms in selected patients, 1-3 surgical success depends on the continued patency of grafts, and graft failure has been associated with worse outcomes. 4,5 Saphenous vein grafts remain the most widely used conduit during CABG, and rates of vein graft failure (VGF) during the first 12 to 18 months after surgery have been reported to be as high as 25%. 6-10 …”
mentioning
confidence: 99%
“…1 Although CABG improves survival and symptoms in selected patients, 1-3 surgical success depends on the continued patency of grafts, and graft failure has been associated with worse outcomes. 4,5 Saphenous vein grafts remain the most widely used conduit during CABG, and rates of vein graft failure (VGF) during the first 12 to 18 months after surgery have been reported to be as high as 25%. 6-10 …”
mentioning
confidence: 99%
“…[1][2][3] More importantly, investigators have demonstrated an association between early vein GF and adverse clinical events. [4][5][6] As such, total arterial revascularization has been advocated. 7 However, in clinical practice, this technique is commonly underused.…”
mentioning
confidence: 99%
“…1 In this issue of Circulation, Hess and colleagues 2 report insights from the PREVENT IV study on VGF after CABG surgery. This is the 11th study published in a major journal reporting results of the PREVENT IV study [3][4][5][6][7][8][9][10][11][12] and involves the same patients. The angiographic results were analyzed from different clinical angles.…”
Section: The Prevent IV Studymentioning
confidence: 99%